Tribological properties of carbon reinforced and silica reinforced FKM against AISI 304 L. (2021) - Tripathi, Navneet; Parthasarathi, N.L.; Eswaramoorthy, M.; Borah, Utpal
Abstract: Fluoroelastomers (FKM) are used as a wheel material for in-service inspection, ISI vehicle as well as in leak resistance barriers in rotating plugs in sodium-cooled, pool type, 500 MV(e), Prototype fast Breeder reactor, PFBR. The wheel lining material is vulnerable to sliding wear failure due to the adverse operating conditions. The FKM rubber is reinforced by carbon and silica to enhance the sliding wear resistance. Dry sliding wear characteristics of Fluoroelastomers are studied at varying load condition and sliding speed by Pin on Disc experiment against an austenitic stainless steel AISI 304 L disc as a counter body. Sliding wear plots are recorded and correlated with various wear parameters. It was found that the carbon-reinforced FKM shows greater wear resistance and better frictional characteristics compared to silica-reinforced FKM on dry sliding wear tests. The outcome of this research will be significant in the development of FKM wheel lining of ISI vehicle of the PFBR in friction as well as wear perspective.